Force Field Analysis in the Development of Tourism in Bukit Tawap, Pagar Batu Village - Alfiyah, Nur Inna; Tini, Dwi Listia Rika; Resdiana, Enza (Yayasan Ilomata, 2025)
Force field analysis (FFA) is a new method that is still rarely used by researchers, so in this study this method is used to determine various driving and inhibiting factors in efforts to develop Bukit Tawap tourism in Pagar Batu village. Because the beginning of the establishment of this tourist attraction experienced a lot of rejection and opposition from the people of Pagar Batu Village. This study was conducted to find out how to develop Bukit Tawap tourism in Pagar Batu Village using the force field analysis method so that later it can be known what factors make Bukit Tawap tourism develop. This study uses the force field analysis method by emphasizing three analysis steps. First, the theme elders who gave birth to a policy, second, giving scores to various factors in the Bukit Tawap tourism development process. Finally, providing analysis using data, theory and documentation. The results of the analysis show that the use of the FFA method is able to provide convenience in mitigating supporting and inhibiting factors so as to produce strategies such as adding available facilities such as selfie spots and play facilities for children, adding tourism promotions on social media, collaborating with tourism actors and collaborating with telecommunications parties to improve technological infrastructure. Meanwhile, to facilitate accessibility, it is necessary to provide transportation facilities to the Bukit Tawap tourist attraction